Research on numerical simulation and integrated die casting process of large complex thin-walled aluminum alloy automobile rear floor - Jian Dong; Jufu Jiang; Ying Wang; Tianxiang Qin; Minjie Huang; Jingbo Cui; Xiaodong Zhang; Lingbo Kong; Junliang Chen (Results in Engineering)
The integrated die-casting rear floor (IDCRF) is a key technology for achieving lightweight, high-efficiency manufacturing in new energy vehicles. In this study, ProCAST was used to simulate the IDCRF forming process. Initial results revealed issues with delayed and asymmetric filling, leading to significant shrinkage porosity. Optimization of the gating system reduced the shrinkage volume from 368 cm3 to 270 cm3, achieving a 26.6 % decrease. To further minimize defects, a response surface methodology (RSM) was employed to analyze the effects of key process parameters. The results showed that pouring temperature had the greatest influence on shrinkage porosity, followed by mold temperature, fast injection speed, and slow injection speed. The optimal parameters determined by the RSM were: 693.5 °C pouring temperature, 186.7 °C mold temperature, 5.0 m s-1 fast injection speed, and 0.40 m s-1 slow injection speed. Under these conditions, the shrinkage porosity volume was further reduced by 59.1 %, and simulation results closely matched predictions. Mechanical testing of castings formed under optimal conditions showed excellent properties near the injection chamber, with a yield strength of 130.1 ± 4.6 MPa, ultimate tensile strength of 266.2 ± 1.9 MPa, and elongation of 11.1 ± 0.51 %. These findings demonstrate a robust simulation-based optimization strategy for improving quality and performance in large-scale integrated aluminum alloy die casting.